38.2: Comparative Analysis of Alignment Characteristics of Polyimide Films Using Near Edge X‐ray Adsorption Fine Structure. Issue 1 (1st July 2013) - Kwak, Musun; Kim, Kyoungri; Choi, Seungkyu; Kim, Nakwon; Kang, Dongwoo; Choi, Youngseok; Jeon, Suho; Kim, Kijeong; Kim, Bongsoo
Abstract We studied the structural characteristics of poly imides (PI) chains according to the film thickness and the temperature treatment using the angle resolved near edge X‐ray adsorption fine structure (AR‐NEXAFS). The molecular directional angle a of the twisted nematic (TN) and the in‐plane switching (IPS) mode alignment film (AF) decrease the tilt angle as increasing the film thickness. These films also shows the temperature dependence of C=C * according to the annealing conditions. In case TN mode sample lost its angular dependency after annealing 230 °C for 2400 sec on the hot plate, but IPS mode sample maintained its angular dependency after same annealing condition with TN mode sample.